Analysing Company Policies at PT. Semen Baturaja Tbk - Elinda Nurul Hasana Dewi B. S.; Intania Syafrina; Irene Juwita Depari; Nina Pramita; Tiara Annisah (Indonesian Journal of Multidisciplinary Science, 2022)
When it was founded on November 14, 1974, the company was born under the name PT Semen Baturaja (Persero) with a 45% share ownership owned by PT Semen Gresik and 55% PT Semen Padang. The company runs a business specifically in the production of slag with the production center located in Baturaja, South Sumatra. Meanwhile, the cement milling and bagging process are carried out at the Baturaja Factory, Palembang Factory, and Panjang Factory which are then distributed to the Company's marketing areas. PT Semen Baturaja (Persero) Tbk is a company engaged in the cement industry and is aware of the risks arising from its operations to workers and the environment. The COVID-19 pandemic period greatly affected the company's work system in all fields, including the PT. Semen BATURAJA Tbk, because many projects are delayed or constrained. By developing corporate strategy, improving employee performance, conducting periodic checks on corporate governance in detail, and increasing the efficiency of the use of raw materials.